2006
DOI: 10.1080/02772240600605087
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of polybrominated diphenyl ether (PBDE) congeners in human blood and milk

Abstract: Polybrominated diphenyl ethers (PBDEs) are brominated flame retardants (BFRs) which have recently been detected in human blood and milk in the USA, and presently these PBDE levels are found to be the highest globally. On a population basis, individual blood and individual milk analyses show similar congener patterns and levels. Until now, there has not been a study comparing PBDE levels in milk and blood of the same individuals. This study is the first to report these levels for PBDEs, though partitioning betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…Our present results show that the ratio of BDE congener levels in serum and in breast milk is around 1 for low-and medium-brominated PBDEs but increases from six bromines and upwards. This is generally supported by earlier studies on serum/breast milk PBDE ratios (Inoue et al, 2006;Schecter et al 2006;LaKind et al, 2009;Schecter et al, 2010: Needham et al, 2011, results that were compiled by Mannetje et al (2012). In the review by Mannetje, the reported serum/milk ratios for BDE-209 ranged from 10 to 40, and the ratio found for BDE-209 in the present study (17) was within that range.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our present results show that the ratio of BDE congener levels in serum and in breast milk is around 1 for low-and medium-brominated PBDEs but increases from six bromines and upwards. This is generally supported by earlier studies on serum/breast milk PBDE ratios (Inoue et al, 2006;Schecter et al 2006;LaKind et al, 2009;Schecter et al, 2010: Needham et al, 2011, results that were compiled by Mannetje et al (2012). In the review by Mannetje, the reported serum/milk ratios for BDE-209 ranged from 10 to 40, and the ratio found for BDE-209 in the present study (17) was within that range.…”
Section: Discussionsupporting
confidence: 88%
“…Of special interest could be the body burdens of BDE-209 in US and Canadian populations, as we know from other investigations that the PBDE exposure in these regions often could be significant (Mazdai et al, 2003;Trudel et al, 2011). However, the few published studies suggest comparably low BDE-209 levels in US individuals, with maximum serum levels in adults of 9.4, 6, and 3.2 (the latter median 0.33) ng/g l.w., respectively (Schecter et al, 2006;Johnson et al, 2010, Lunder et al, 2010. However, differences in analytical quality (including quantification limits) between BDE-209 studies make comparisons rather uncertain.…”
Section: Discussionmentioning
confidence: 96%
“…This difference between milk and blood for BDE-153 has also been observed in Norwegian milk, where the relative amount of BDE-153 was lower in breast milk compared to serum [47]. Similar results have also been reported from the US where the partitioning between blood and milk was studied, and these data suggest that it may be easier for the less brominated congeners to move from blood to milk [48]. The transfer from blood to milk seems therefore less efficient for higher brominated diphenyl ethers than for the lower brominated diphenyl ethers.…”
Section: Discussionsupporting
confidence: 83%
“…Settled sediments from lakes and undisturbed (preferably anoxic) sediments represent a historical record of contaminant Baumann et al, 2003;Bi et al, 2006;Bordajandi, Abad and Gonz alez, 2008;Darnerud et al, 2002;Eslami et al, 2006;Fangstrom et al, 2004;F€ urst, 2006;Jaraczewska et al, 2006;Kalantzi et al, 2004;Ryan et al, 2002;Schechter et al, 2003Schechter et al, , 2006Strandman, Koistinen and Vartiainen, 2000;Sudaryanto et al, 2005;Toms et al, 2007;Tsydenova et al, 2007 concentrations scavenged from the overlying waters by sediment particles, which are later deposited in the bed sediments. Three dated sediment cores from locations in western Europe (the Drammenfjord in Norway, the western Wadden Sea in the Netherlands and Lake Woserin in Germany) analysed for 14 BDE congeners showed a time-dependent pattern in BDE distribution .…”
Section: Environmental Levels -Present Past and Future Temporal Trendsmentioning
confidence: 99%